1990
DOI: 10.1192/bjp.156.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity in an Accident and Emergency Department

Abstract: In order to evaluate how many patients presenting at accident and emergency (A&E) departments show signs of psychiatric disturbance, 140 consecutive medical presentations to an A&E department were evaluated using a range of simple self-report and rater measures, then followed up a month later. High levels of reported psychological problems were detected at screening, and these persisted at follow-up. Correlates of psychological disturbance and repeated attendance at A&E were investigated, indicating the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…Two larger European studies and one UCLA study of patients presenting to emergency departments found prevalence rates of mental illness ranging from 13.6% for mood disorders in an Italian ED to 46% for at least one psychiatric diagnosis in the UCLA ED. 15, 39, 40 …”
Section: Introductionmentioning
confidence: 99%
“…Two larger European studies and one UCLA study of patients presenting to emergency departments found prevalence rates of mental illness ranging from 13.6% for mood disorders in an Italian ED to 46% for at least one psychiatric diagnosis in the UCLA ED. 15, 39, 40 …”
Section: Introductionmentioning
confidence: 99%
“…The Department of Health (1994) clearly ascribes an opportunistic role to the A&E nurse in the assessment and promotion of mental health. Research has demonstrated that psychological problems are particularly prevalent amongst attendees of A&E (Salkovskis, Storer, Atha, & Warwick, 1990), and an estimate from the Manchester and Salford self-harm project (MASSH) suggested that 50% of people attending A&E with deliberate self-harm were not currently engaged with psychiatric services (Cooper & Appleby, 1998).…”
mentioning
confidence: 99%
“…Además, el periodo en el que se examina al paciente corresponde a los últimos siete días. El coeficiente ˛ de Cronbach para las versiones alemana y neozelandesa de la escala va de 0.81 a 0.90 (Herrmann, Buss y Snaith, 1995;Salkovskis, Storer, Atha y Warwick, 1990), lo que denota que posee buena consistencia interna. La confiablidad test-retest, después de dos semanas, fue r > 0.80 (Herrmann et al, 1995), lo que indica la estabilidad de la medida en el tiempo.…”
Section: Escala Hospitalaria De Ansiedad Y Depresiónunclassified
“…Por el contrario, en el caso de los ítems inversos (4, 8, 10, 12, 13 y 14), las opciones de respuesta que denotan ausencia o negación (e. g., nunca, nada, no) se califican con 3, mientras que las respuestas que denotan presencia o afirmación (e. g., habitualmente, mucho, muy frecuentemente, sí), se califican con 0. Al final se hace un sumatorio de los 14 ítems y se obtiene el resultado total de la escala, que puede ir desde 0 hasta 42, en tanto que la puntuación por cada una de las dos subescalas (Ansiedad y Depresión) puede ir desde 0 hasta 21, y de acuerdo con estas se determina si la persona presenta o no ansiedad o depresión (o ambas) y en qué grado, con base en los rangos siguientes: 0-7 = ausencia, 8-10 = presencia de síntomas asociados al trastorno, y 11-21 = cuadro clínico completo (Snaith, 2003).…”
Section: Instrumentounclassified